2008
DOI: 10.1590/s0103-84782008000600004
|View full text |Cite
|
Sign up to set email alerts
|

Abordagem Bayesiana das curvas de crescimento de duas cultivares de feijoeiro

Abstract: IIAbordagem Bayesiana das curvas de crescimento de duas cultivares de feijoeiro RESUMO Neste trabalho foi utilizada a metodologia Bayesiana para ajustar o modelo não-linear logístico para dados de crescimento de duas cultivares de feijoeiro INTRODUÇÃOGeralmente o estudo de curvas de crescimento de espécies vegetais tem sido conduzido por meio de uma abordagem freqüentista, ajustandose modelos não-lineares que buscam sintetizar as informações em poucas estimativas de parâmetros interpretáveis biologicament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 2 publications
1
11
0
8
Order By: Relevance
“…A similar result was reported by Puiatti et al (2013), who identified and grouped the nonlinear regression models that best fitted the description of the total dry matter accumulation of garlic plant over time, where L showed better performance than that of the B, G, L, M, M1, M2, vB, and Meloun III models. The L model fitted the data well in several experiments with nonlinear regression models, for the description of growth curves or nutrient accumulation, as in Pôrto et al (2007) for onion cultivation, Maia et al (2009) for banana trees, and Martins Filho et al (2008) who also reported great adjustments for the L model using the Bayesian methodology for the growth data of two bean cultivars.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…A similar result was reported by Puiatti et al (2013), who identified and grouped the nonlinear regression models that best fitted the description of the total dry matter accumulation of garlic plant over time, where L showed better performance than that of the B, G, L, M, M1, M2, vB, and Meloun III models. The L model fitted the data well in several experiments with nonlinear regression models, for the description of growth curves or nutrient accumulation, as in Pôrto et al (2007) for onion cultivation, Maia et al (2009) for banana trees, and Martins Filho et al (2008) who also reported great adjustments for the L model using the Bayesian methodology for the growth data of two bean cultivars.…”
Section: Resultsmentioning
confidence: 88%
“…Nonlinear regression models have been shown as adequate to describe these curves, both by the frequentist and by the Bayesian approaches, which have parameters with biological interpretation, such as asymptotic weight and growth velocity (Martins Filho et al, 2008). Puiatti et al (2013) and Reis et al (2014) indicated high-fitting quality for the logistic, Gompertz, and Von Bertalanffy models, in garlic accessions, using the frequentist approach.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling works on vegetables as well as on beans aim to evaluate all the cycle of a specific species or to model the growth of different cultivars or according to the application of different cultural managements (Urchei et al, 2000;Martins Filho et al, 2008;Vieira et al, 2008;Vieira Neto et al, 2013).…”
Section: Palavras-chavementioning
confidence: 99%
“…O ajuste de modelos não-lineares, do ponto de vista metodológico, é bastante explorado por diversos autores nas mais diversas áreas, por meio das abordagens clássicas (SAVIAN et al, 2007a(SAVIAN et al, , 2007bMENDES, et al, 2008;MAIA et al, 2009;) e bayesiana (MUNIZ et al, 2007;MARTINS FILHO et al, 2008;SILVA et al, 2008;SAVIAN et al, 2009). Na análise de regressão usual, geralmente, não se usa uma informação a priori sobre uma possível relação de ordem na variável resposta.…”
Section: Dentro Do Contexto Nutricional a Suplementação De Micromineunclassified